The ‘Critical - Creative’ Divide in Academia: Are They Allies or Strange-Bed-Fellows? - Kaguhangire-Barifaijo, Maria; Karyeija, Gerald K.; Komakech, Robert Agwot; Kyohairwe, Stella B.; Oryema, Dan E. (Advances in Social Sciences Research Journal, 2022)
The paper confronts the most controversial debate regarding the “Critical and Creative Thinking” divide, often termed as ‘strange bedfellows’ in academia. The divide is manifested in the way academics often bristle at the suggestion that exists between ‘critical and creative thinking perceptions. We argue that creativity without critical judgment would be fanciful, impractical and ridiculous, with the potential to run other people’s ideas ‘amok’, while critical thinkers would get short shrift if only they were reduced to just critiquing. Hence, it is necessary to have both on the team, those who can create novel ideas and others to critique others’ creations. While we acknowledge the distinction of the concepts, their roles are complementary and necessary to create a balance that must co-exist and shine in the scholarly arena. We conclude that the phrases often used in academia, such as; ‘devil’s advocates’, ‘opponents’ or ‘critical reviewers’ of doctoral candidates or in peer reviews has apparently been taken literally. We recommend that the superficial misconception of ‘greater’ or ‘superior’, is an unnecessary cognitive dissonance that must be resolved to promote co-existence for greater results.